Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2014
Wykonaj mnożenie i zredukuj wyrazy podobne 4.33 gwiazdek na podstawie 6 opinii

Wykonaj mnożenie i zredukuj wyrazy podobne

1Zadanie
2Zadanie
3Zadanie
4Zadanie
5Zadanie
6Zadanie
7Zadanie

`a)\ (2x^2+1)(x^2+3)=` `2x^2(x^2+3)+1(x^2+3)=` 

`\ \ \ =2x^4+6x^2+x^2+3=` `2x^4+7x^2+3` 

 

`b)\ (3x^3+2)(x^3-4)=` `3x^3(x^3-4)+2(x^3-4)=` 

` \ \ \ =3x^6-12x^3+2x^3-8=`  `3x^6-10x^3-8` 

 

`c)\ (3a^2-b)(a^2-2b)=` `3a^2(a^2-2b)-b(a^2-2b)=` 

`\ \ \ =3a^4-6a^2b-a^2b+2b^2=` `3a^4-7a^2b+2b^2` 

 

`d)\ -4(a-2b)(2b-a)=` `(-4a+8b)(2b-a)=` 

`\ \ \ =-4a(2b-a)+8b(2b-a)=` 

`\ \ \ =-8ab+4a^2+16b^2-8ab=` `4a^2+16b^2-16ab` 

 

`e)\ (2x^2-3y^2)(2x^2+3y^2)=` `2x^2(2x^2+3y^2)-3y^2(2x^2+3y^2)=` 

`\ \ \ =4x^4+6x^2y^2-6x^2y^2-9y^4=` `4x^4-9y^4` 

 

`f)\ -3(x-2y^2)(y-x^2)=` `(-3x+6y^2)(y-x^2)=` 

`\ \ \ =-3x(y-x^2)+6y^2(y-x^2)=` 

`\ \ \ =-3xy+3x^3+6y^3-6x^2y^2`